Measuring Risk Factor Analysis Using PCA Method In Batik Businiess (Case Study: SMEs Batik Cirebon) - Alya Az Zahraa; Naniek Utami Handayani; Sri Hartini; Ratna Purwaningsih (Advance Sustainable Science Engineering and Technology, 2023)
The number of business units that sell Batik creates a very high level of competition so that they are required to find alternatives or solutions to be superior to competitors. In addition, it is also necessary to manage business risks and pay attention to factors that support the risk of the Batik fashion business they are running. The purpose of this study was to determine and categorize the main factors supporting the risk of fashion Batik business in Cirebon. This study uses 15 initial variables of Batik fashion business risk which will be tested by means of factor analysis. The method used is Principal Component Analysis (PCA) with SPSS software. Data collection techniques using questionnaires and interviews. The sample used was 50 random respondents in the Batik fashion business unit in Cirebon. Four main factors were obtained from the variables that have been identified in the risk of Cirebon Batik fashion business. Factor 1 is called operational factors, factor 2 is called financial factors, factor 3 is called strategic factors, and factor 4 is called external factors